The Gender Gap in Mental Health: Immigrants in Switzerland - Simona, Jehane; Pecoraro, Marco; Ruedin, Didier (New York: Springer, 2014)
Introduction: Many aspects of health differ significantly between men and women, including mental health where there are pronounced differences. Women are more likely than men to seek treatment for psychological problems and depression. Main: In the literature, two broad explanations are offered for these gender differences. On the one hand, socio-economic factors such as the position in the labor market are highlighted. On the other hand, differences in mental health are associated with aspects of social capital, such as the support individuals receive from others. Immigrant populations are ideal to study these mechanisms, as they display great variance in both dimensions. Here we show that both mechanisms contribute to reported mental health. Discussion: Statistically speaking, socio-economic factors and the perception that one is in control of one’s life can explain substantial parts of the gender differences in mental health. Of the socio-economic variables, the most important covariates are the level of education and labor market status. Indeed, there does not appear to be anything particular about immigrant populations as is sometimes suggested in migration studies. Implications: These results follow that policies to alleviate the gender gap in mental health will probably be most successful if they focus on improving health and well-being generally rather than focusing on gender or being of immigrant origin. For immigrants and non-immigrants alike, this means facilitating labor force participation such as by aiding reintegration and training for low-skilled women.